2013
DOI: 10.1021/ct400773k
|View full text |Cite
|
Sign up to set email alerts
|

Range-Separated DFT Functionals are Necessary to Model Thio-Michael Additions

Abstract: The textbook mechanism for the addition of a thiol to an olefin is the Michael-type addition, which involves a nucleophilic attack of a thiolate anion on an alkene to form a carbanion intermediate. Previous computational models of these reactions have proposed alternative mechanisms, as no minimum corresponding to the carbanion intermediate was present on the potential energy surface. We show that many popular pure and hybrid DFT functionals, such as PBE and B3LYP, erroneously predict that the carbanion is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
109
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(124 citation statements)
references
References 51 publications
6
109
0
Order By: Relevance
“…25,26 The correct description of CT requires the use of either global hybrids with a large fraction of exact exchange equal to or exceeding 50%, or range-separated hybrid functionals with correct long-range asymptotics. 15,26,27 A similar requirement is found for the accurate modeling of charge-transfer excitations in time-dependent DFT. 18,19 The errors associated with charge transfer are present in other noncovalently bonded systems such as radical-molecule complexes, 26,27 anion-molecule complexes, 27 and solvated-electron systems.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…25,26 The correct description of CT requires the use of either global hybrids with a large fraction of exact exchange equal to or exceeding 50%, or range-separated hybrid functionals with correct long-range asymptotics. 15,26,27 A similar requirement is found for the accurate modeling of charge-transfer excitations in time-dependent DFT. 18,19 The errors associated with charge transfer are present in other noncovalently bonded systems such as radical-molecule complexes, 26,27 anion-molecule complexes, 27 and solvated-electron systems.…”
Section: Introductionmentioning
confidence: 68%
“…15,26,27 A similar requirement is found for the accurate modeling of charge-transfer excitations in time-dependent DFT. 18,19 The errors associated with charge transfer are present in other noncovalently bonded systems such as radical-molecule complexes, 26,27 anion-molecule complexes, 27 and solvated-electron systems. 28 Recent articles by Kozuch and Martin 12 and Bauzáet al 29 stated that dispersion-corrected functionals are unable to represent halogen bonding interactions accurately.…”
Section: Introductionmentioning
confidence: 68%
“…Range-separated functionals have been shown to cure delocalization errors of standard functionals in Michael-type reactions [SAR13], but HF-DFT should also work, while bypassing the need to introduce a system-dependent parameter. Other authors have suggested constraining the potentials of DFT calculations with the correct asymptotic forms [GL12], which is another approach ripe for energy-error analysis.…”
Section: E Applications Of Energy-error Analysis and Other Approachesmentioning
confidence: 99%
“…Computational workflows have been developed to calculate if a molecule containing an electrophilic warhead has a geometry that can fit in the active site of a protein target when the cysteine adduct has formed, but these methods are based on mechanical models and cannot describe the relative reactivity of the warhead [15,[19][20][21]. A recent study by our group determined that many common DFT methods fail to correctly describe the carbanion intermediate and underestimate the stability of the products [22]. This failure has limited the utility of standard DFT functionals.…”
Section: Introductionmentioning
confidence: 99%